A hybrid scheduler for many task computing in big data systems - Vasiliu, Laura; Pop, Florin; Negru, Catalin; Mocanu, Mariana; Cristea, Valentin; Kołodziej, Joanna (Zielona Góra: Uniwersytet Zielonogórski)
With the rapid evolution of the distributed computing world in the last few years, the amount of data created and processed has fast increased to petabytes or even exabytes scale. Such huge data sets need data-intensive computing applications and impose performance requirements to the infrastructures that support them, such as high scalability, storage, fault tolerance but also efficient scheduling algorithms.
Keywords: many task computing; scheduling heuristics; QoS; big data systems; simulation